How Do Own and Siblings’ Genders Shape Caregivers’ Risk of Perceiving Care-Related Criticism From Siblings? - Rurka, Marissa M; Suitor, J Jill; Gilligan, Megan; Frase, Robert T (The journals of gerontology. Series B, Psychological sciences and social sciences, 2023)
Abstract Objectives Caring for a parent takes a greater psychological toll on daughters than sons. To minimize the psychological burden of parent care, it is important to understand what contributes to this gender disparity. Inspired by the caregiver stress process model and gender-as-relational perspective, we investigate how caregivers’ gender, and the genders of their siblings, shape their risk of perceiving care-related criticism from siblings, a secondary stressor of caregiving with negative implications for psychological well-being. Methods Using data from 408 adult child caregivers nested within 231 families collected as part of the Within-Family Differences Study, we employ multilevel modeling to examine how caregivers’ gender, as well as the gender composition of their sibship, interact to shape caregivers’ probability of perceiving criticism from siblings regarding the care that they provide their mother. Qualitative data from the same caregivers are then analyzed to illuminate processes underlying these statistical associations. Results Quantitative analyses reveal that daughters in predominantly-son sibships have a lower risk of perceiving care-related criticism than daughters in sibships with higher proportions of daughters. Qualitative analyses elucidate these findings. Daughters in predominantly-son sibships report that their siblings defer to them regarding their mother’s care. Conversely, daughters in higher proportion-daughter sibships perceive care-related criticism because they and their sibling(s) hold conflicting views regarding care, and there is less consensus regarding who best understands their mother’s care needs and preferences. Discussion Findings demonstrate how characteristics of caregivers and their sibships interact to affect caregivers’ risk of perceiving criticism regarding their care to their mothers.